An experimental evaluation of the leaching kinetics of PGM-containing Ni–Cu–Fe–S Peirce Smith converter matte, under atmospheric leach conditions - van Schalkwyk, R.; Eksteen, Jacques; Petersen, J.; Thyse, E.; Akdogan, G. (Elsevier, 2011)
In a first stage atmospheric leach in a typical Sherritt Ni–Cu matte leach process, a Ni–Cu–Fe–S Peirce Smith converter matte is contacted with recycled copper spent electrolyte (an aqueous copper sulphate/sulphuric acid solution) at 85 °C with the purpose of dissolving nickel, while simultaneously removing copper from solution. In the PGM industry, copper removal is also important because it serves as a leading indicator in the removal of Ir, Rh, and Ru from the spent electrolyte. The matte mainly consists of heazlewoodite, chalcocite/djurleite, a Ni–Cu alloy phase and inert spinel minerals (magnetite and trevorite). Nickel is leached from the matte by two mechanisms: (i) leaching by sulphuric acid and oxygen; and (ii) an anaerobic metal exchange reaction (cementation and metathesis) between cupric ions in solution and nickel in the matte, which is also responsible for the removal of copper from solution.This study investigates the oxidative and non-oxidative leaching of converter matte in a laboratory batch reactor, with attention specifically being given to the effects of initial copper and acid concentrations and their effects on leaching kinetics. Experimental conditions were varied based on a 2N experimental design. The availability of oxygen for acid-leaching reactions was found to be the most important factor influencing copper removal and nickel extraction. A 63% nickel extraction could be achieved during oxidative tests vs. 22% in a non-oxidative test. This also indicates that cementation did not take place to a significant degree and that nickel leaching mostly took place via leaching by acid and oxygen. It is suspected that the low degree of copper removal can be attributed to the solids/reactants ratio was employed in tests. The initial copper and acid concentrations did not have a significant effect on the rate of nickel extraction or the total amount of nickel extracted. The rate of copper removal was not significantly influenced by the initial copper concentration, but copper removal was affected by the initial acid concentration. In oxidative tests with high initial acid concentrations, the rate at which copper was leached from the matte was faster than the rate of cementation. The results suggest that operating under high initial acid conditions could interfere with copper removal with no significant benefit in terms of nickel extraction. The results allow the regression of rate expressions.